Measurement and Comparison of Costs of Hypertensive Patients Aged 40-89 Years Treated with Lisinopril and Perindopril - Joana Simeonova; Snejanka Tisheva-Gospodinova; Yoana Todorova; Petkana Hristova; Asia Yanakieva; Martin Hristov (Journal of Biomedical & Clinical Research, 2018)
A cross-sectional study was carried out in 2016 in the research project No 4/2016. We selected 98 patients aged 40-89 and diagnosed with hypertension. The patients were admitted to Cardiology Clinic One of the University Hospital in Pleven. The study aimed to measure and compare direct and indirect costs of hypertensive patients aged 40-89 years, who were treated with lisinopril and perindopril. We estimated the total and average costs of 50 (51.0%) patients treated with lisinopril and 48 (49.0%) treated with perindopril. Males were 46.4%, and the mean age of the sample was 65.9.0±11.2 years. Data were processed by Statistical Package for Social Science version 19.0 (SPSS.v.19.0). Total costs exceeded amount reimbursed for the clinical path (BGN 420.00) in 64.6% of the patients treated with perindopril and 48.0% of the patients treated with lisinopril. We found that treatment costs within 6-months after discharge were BGN 673.82 in patients treated with lisinopril, as compared to BGN 171.92 reimbursed by the National Health Insurance Fund (NHIF), and BGN 781.18 for those treated with perindopril, compared to BGN 216.33 reimbursed by NHIF. The NHIF reimbursement rate for antihypertensive treatment is insufficient to cover all direct costs. Increased hospital costs and out-of-pocket payments present a significant restriction on access to treatment for arterial hypertension.